Mini obstacle avoidance robot using peripheral interface controller (PIC) / Khairul Nizam Abdul Halim - Abdul Halim, Khairul Nizam (2006)
This thesis focuses on building obstacle avoidance mechanism for mobile robot that will safely and reliably navigate in the close proximity of obstacles and in confined space, while using range sensor for real-time obstacle detection. The robot provides a collision free movement by detecting the obstacles thus avoiding it. The movement was controlled by the microcontroller, base on information from sensors. A program using Peripheral Interface Controller (PIC) was developed to control the movement of the robot. The program included the modeled obstacles avoidance and collision-free maneuvers when moving. The program was implemented to the physical robot to demonstrate its efficiency. MPLAB was used to develop the software for the controller and the microcontroller is PIC16F84A.